Biointerface by cell growth on layered graphene–artificial peroxidase–protein nanostructure for in situ quantitative molecular detection - Guo, Chun Xian (2012)
A smart multifunctional biointerface with dimensional compatibility and good electrical conductivity is constructed by growing human breast adenocarcinoma cells on layered graphene–artificial peroxidase–extracellular matrix protein and further used to in situ selectively and quantatively detect reactive oxygen species, for the first time discovering that the number of extracellular released hydrogen peroxide molecules is around 1011 per cell.